British Philhellenism and the Historiography of Greece: A Case Study of George Finlay (1799-1875) - Potter, Liz (The Historical Review/La Revue Historique, 2005)
This article offers a case study of George Finlay, a British philhellene whose intellectual make-up deserves more attention than it has previously been given (1). Unlike many Western European philhellenes who returned home disillusioned with Greece, Finlay spent his life in Athens (2); and unlike the overwhelmingly classicising Hellenism of his British contemporaries, his was a Hellenism that insisted on the interest and instructiveness of the history of Greece from the Roman period onwards (3). From a study of his History of Greece BC 146 to AD 1864 (4), and an analysis of its influences (5) and its uses (6), the article portrays Finlay as a complex, supple and interesting thinker. He is of particular interest to the nineteenth-century historian of political ideas for the ways in which he inherited and re-shaped ideas associated with civic virtue, philosophic history and contemporary liberalism.